2010
DOI: 10.1194/jlr.m007948
|View full text |Cite
|
Sign up to set email alerts
|

Involvement and mechanism of DGAT2 upregulation in the pathogenesis of alcoholic fatty liver disease

Abstract: This article is available online at http://www.jlr.org Alcoholic liver disease (ALD) continues to be an important health problem in the United States. Although much progress has been made over the past two decades, the mechanisms involved in its initiation and progression remain to be fully understood. The disease is characterized by early steatosis, subsequent steatohepatitis (steatosis with infl ammatory cell infi ltration and necrosis), and, in some instances, progression to fi brosis and/or cirrhosis ( 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…A recent study in pigs, in which the DGAT2 gene is 90% identical to the homologous gene of humans, showed that an A/G variation in the 3 ′ UTR of DGAT2 was resulted in marked reduction in hepatic TG as well as plasma TG, diacylglycerol, and FFA levels ( 11 ). In vitro and animal studies also suggested that upregulation of DGAT2 may be involved in the hepatic fat accumulation induced by chronic alcohol consumption ( 20 ). Niacin was demonstrated to directly and noncompetitively inhibit the activity of DGAT2 in cell lines ( 9 ), and our study is the fi rst to show a signifi cant association between the DGAT2 polymorphism and the liver fat changes in response to niacin treatment in patients with dyslipidemia.…”
Section: Discussionmentioning
confidence: 66%
“…A recent study in pigs, in which the DGAT2 gene is 90% identical to the homologous gene of humans, showed that an A/G variation in the 3 ′ UTR of DGAT2 was resulted in marked reduction in hepatic TG as well as plasma TG, diacylglycerol, and FFA levels ( 11 ). In vitro and animal studies also suggested that upregulation of DGAT2 may be involved in the hepatic fat accumulation induced by chronic alcohol consumption ( 20 ). Niacin was demonstrated to directly and noncompetitively inhibit the activity of DGAT2 in cell lines ( 9 ), and our study is the fi rst to show a signifi cant association between the DGAT2 polymorphism and the liver fat changes in response to niacin treatment in patients with dyslipidemia.…”
Section: Discussionmentioning
confidence: 66%
“…However, administration of TAM decreased DGAT2 expression in CTL mice and both mouse models. DGAT2 is the rate-limiting enzyme catalyzing the final step in triglyceride synthesis and exerts an important role in the development of fatty liver diseases (Choi et al, 2007;Yu et al, 2005;Wang et al, 2010). Thus, these results suggested that TAM did not increase but instead decreased the fat accumulation after the onset of steatosis and NASH.…”
mentioning
confidence: 58%
“…In contrast, MAPK family members such as ERK exert protective and anti-apoptotic effects upon activation by an upstream kinase and regulate a number of major cellular functions, such as cell proliferation, differentiation and inflammation (Czaja et al, 2003). Furthermore, ERK activation is reported to decrease DGAT2 expression (Wang et al, 2010;Tsai et al, 2007). Increased JNK phosphorylation has been reported in steatosis and NASH model mice (Hirosumi et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Small end-products of lipid peroxidation, such as 4-HNE and other aldehydes transported by activated granulocytes/monocytes, may facilitate and maintain generalized inflammation (25). The plasma adiponectin level is determined by complex intracellular regulatory mechanisms involved in gene expression, post-transcriptional/translational modification, and trafficking/secretion processes (26,27). Adiponectin is predominantly produced and secreted into circulation by adipocytes.…”
Section: Discussionmentioning
confidence: 99%